The Role Of The Gresik Regency Regional Government On Of The Stakeholders In Songkok Small And Medium Indsustries (Ikm) In Gresik Regency - Arif Syarifuddin, Mohammad; Pribadiyono, Pribadiyono; Budi Riharjo, Iksan (International Journal of Science, Technology & Management, 2024)
The number of small and medium-sized industries recorded today is 261 people, showing the dominance of the Songkok industry in Gresik Regency. Management with a family and conventional system results in the Songkok Small and Medium Medium Industry Business Actors in Gresik Regency not being able to market Songkok optimally and have not been able to compete in the national market, the involvement of local governments is needed in supporting the development of small and medium industries in Gresik Regency. The existence of a small -medium medium industry in Gresik Regency in addition to being one of the crafts that produces products that become part of the culture of the Indonesian people, is also one of the industries that contribute to economic growth in Kabuoaten Gresik. The research method used is a qualitative method with case studies, a small and medium -sided industry has existed in Gresik Regency since the 1970s, initially only in Gresik District, has grown, developed, and spread in several regions in Gresik Regency, so that it became a part From the icon of Gresik Regency as the largest Songkok Craftsman Center in Indonesia. The reality on the ground with existing experience does not necessarily make the business fears able to compete in the national market. Digging information from 9 informants, aims to identify the Songkok Small and Medium Industry Business Process (IKM) in Gresik Regency, identify the right marketing mix in Songkok Small and Medium Industries (IKM) in Gresik Regency, and see the extent of the role of the local government as one of the stakeholders In supporting the growth of Songkok Small and Medium Industries (IKM) in Gresik Regency. The results of the Songkok Small and Medium Medium Industry Research in Gresik Regency are a family -patterned business with a production and seasonal sales and running business processes conventionally and traditional. Publick Governance as one of the new components in the marketing mix (marketing mix) which also has an important role in the development of the small and medium industry of Songkok in Gresik Regency. Collaboration and Synergy of the Gresik Regency Regional Government as one of the stakeholders with business actors needs to be improved in order to encourage the growth of small and medium industry and songkok industries and efforts to preserve the culture and identity of the Gresik Regency.